PERBEDAAN PENDAPATAN PETANI PADI SAWAH ANTARA ETNIS LOKAL DAN NON LOKAL DI DAERAH IRIGASI SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA - Mega Putri Kesek; Eyverson ., Ruauw; Melissa L.G. Tarore (Sam Ratulangi University, 2017)
The purpose of this study to look at income differences between ethnic Local and Non Local of paddy rice farmers in Sangkub irrigated areas. This study took places in the village of Sangkub Two and Pangkusa Village, Sub-district of Sangkub, District of North Bolaang Mongondow. The study conducted from September to December 2016. Data collection is Primary and Secondary data. The primary data obtained through interviews using a questionnaire to 40 respondent farmers from two different ethnicities. They are 20 persons of Local ethnic and 20 persons of Non Local ethnic using simple random sampling method. Secondary data were obtained from the agencies concerned, namely the North Bolmong District Agriculture Office. The data collected in the study: (1) The characteristics of farmers, (2) Expenditures of the farmer (IDR), Income (IDR). Analysis of data used Analisys of Farm Income and Analysis of average difference by using t-test. The results showed that the income of farmers of paddy between ethnic Local and Non-Local is different where non-local ethnic incomes have higher incomes than the local ethnic.Key words: income differences, paddy rice farmers, Local and Non-Local Non, Sub-district of Sangkub, North Bolaang Mongondow District